Liturgical Dance in Nigeria: Babalola Abiodun and Victory Ashien Works in Focus Samson (2024)
Liturgical dance has its roots in early Christian worship practices. It reached a high point in the medieval church, when a number of religious orders arose with a specific emphasis on prayer and meditation, and it was performed primarily by religious professionals. In many churches and in many liturgical dance groups today, the emphasis is on performance in service or in festivals. The performance groups many times feature extensive and complicated choreography that showcases the style of the choreographer and the skills of the dancers. But what is liturgical dance supposed to be? What are the specific nature and forms of liturgical performances in Nigeria? Adopting the Religion Theory of Ninian Smart and Performance Analysis, this research focuses on the process of choreographing/creating liturgical dances, the impact of other elements of performance on liturgical dance creation, spiritual impact on liturgical dance and fully on the performance aspect of liturgical dance. The performance analysis is based on the interviews conducted, and having analysed two liturgical performance videos and conducting interviews on two liturgical choreographers, namely Victory Ashien of Spirit of David, Nigeria and Babalola Abiodun of Praise Dance Academy. Based on the above, this research concludes that liturgical dance in Nigeria is on the rise and there is a significant interest from different groups and churches. Besides, these liturgical dance performances embrace theatrical dance performance elements in communicating and interpreting stories.